2011
DOI: 10.1111/j.1574-6968.2011.02406.x
|View full text |Cite
|
Sign up to set email alerts
|

Just scratching the surface: an expanding view of the Cpx envelope stress response

Abstract: To detect and effectively respond to damage to the cell envelope, Gram‐negative bacteria possess multiple envelope stress responses. Among these, the CpxAR two‐component system has been shown to sense the presence of misfolded periplasmic proteins and increase the production of envelope‐localized protein folding and degrading factors in response. However, recent studies have revealed that additional parameters, such as adhesion and central metabolism, can also be sensed by the Cpx signalling system. The discov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
197
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(202 citation statements)
references
References 84 publications
(135 reference statements)
3
197
0
1
Order By: Relevance
“…This system responds to a broad range of stimuli related to perturbations in the bacterial cell envelope, including salts, metals, pH, lipids and misfolded proteins. The fact that both the YeO3-DrfaH and YeO3-c-R1 strains showed significant downregulation of the periplasmic repressor CpxP and higher levels of the CpxR protein indicated that bacteria respond to changes in cell wall integrity (Hunke et al, 2012;Vogt & Raivio, 2012). Overall, our data did not indicate massive alterations in the expression of membrane proteins, and transcriptomics and quantitative proteomics do not allow us to draw any conclusions about the state of the proteins.…”
Section: Discussionmentioning
confidence: 55%
“…This system responds to a broad range of stimuli related to perturbations in the bacterial cell envelope, including salts, metals, pH, lipids and misfolded proteins. The fact that both the YeO3-DrfaH and YeO3-c-R1 strains showed significant downregulation of the periplasmic repressor CpxP and higher levels of the CpxR protein indicated that bacteria respond to changes in cell wall integrity (Hunke et al, 2012;Vogt & Raivio, 2012). Overall, our data did not indicate massive alterations in the expression of membrane proteins, and transcriptomics and quantitative proteomics do not allow us to draw any conclusions about the state of the proteins.…”
Section: Discussionmentioning
confidence: 55%
“…The Cpx regulon contains approximately equal numbers of upregulated and downregulated genes, including those for pilus assembly, efflux pump biogenesis, adherence, antibiotic resistance, virulence and biofilm development (Vogt & Raivio, 2012). The deletion of cpxAR increased not only the expression of pecS and pecM (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The set of genes involved in phosphate metabolism and transport responds to cellular phosphate limitation, which may occur in the induced cell; the involvement of pho genes in lambda growth has been noted (25). The genes cpxP, htpX, and degP are activated by the two component system encoded by cpxR/ A, which senses envelope stress (26), a plausible response to such phage proteins as the lysis set that are made at late times of induction. Finally, there is a set of up-regulated genes that mostly have known function, but no obvious relation to phage development; examples are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%